Characterization of post-COVID-19 Guillain-Barré syndrome in a private clinic in the inner Amazon – case series report (Research, Society and Development, 2022)
Objectives: to report cases of post-COVID-19 Guillain-Barré Syndrome in a city in the interior of the Amazon, to characterize the evolution of the clinical picture, diagnosis and outcome of the disease, to portray the similarities and differences between patients and to highlight the importance of valuing the Post-COVID-19 Guillain-Barré Syndrome. Methods: this is a case series composed of six patients with a condition compatible with Guillain-Barré Syndrome related to previous infection by COVID-19. It is an observational and descriptive study and the data were collected retrospectively from the analysis of the medical records of a private clinic located in Santarém, state of Pará, Brazil. Results and Discussion: All patients had a clinical and laboratory diagnosis of COVID-19, followed by Guillain-Barré Syndrome. In this study, motor impairment was predominant and did not always follow an ascending pattern. The cerebrospinal fluid (CSF) examination had a variable result and without the typical abnormalities. Electroneuromyography revealed that axonal involvement was predominant. Most patients evolved with functional recovery and only one of them presented no improvement. Treatment with intravenous immunoglobulin appears to have contributed to a positive outcome. The data found are compatible with studies in other regions of the world. Conclusion: Post-COVID-19 Guillain-Barré Syndrome may have different clinical, laboratory and neurophysiological manifestations than usual and may have a variable course, with early diagnosis being essential for a more assertive treatment and lower risk of sequelae. This has become a challenge in remote places and small towns in the Amazon, where access to health care is more precarious.